Technical difficulties of mixed culture driven waste biomass-based biohydrogen production: Sustainability of current pretreatment techniques and future prospective - Karim, Ahasanul; M., Amirul Islam; Puranjan, Mishra; Yousuf, Abu; Che Ku Mohammad, Faizal; Khan, Md. Maksudur Rahman (Elsevier, 2021)
Biohydrogen production from different types of waste biomass using mixed culture inoculum has been an active research area in recent years. Several emerging techniques has been studied targeting to achieve higher efficiency and competitive hydrogen production through the dark fermentation. However, the production of biohydrogen from complex waste biomass meets the setback of lower final product yield due to the low substrate degradation rate. Besides, hydrogen consuming microbes in the mixed culture impede the rate of biohydrogen production. Thus, the waste biomass substrate and microbial inoculum are highly required to pretreat for enhancing system performance. With the aim to gain deeper insight into waste biomass and inoculum pretreatment techniques, this review compiles recently practiced pretreatment techniques with their limitations. The major challenges of these methods and few strategies to overcome these limitations with future directions are discussed in this review. Moreover, the efficiency of a potential nonconventional pretreatment technique such as electroporation (EP) over traditional techniques to degrade the complex waste biomass and reduce the load of hydrogen consuming microbes in the mixed culture consortium was reviewed. This review argued to provide a deeper insight to develop an efficient pretreatment technique by combining traditional techniques and EP for enhancing mixed culture driven biomass-based hydrogen production